Pseudocolouring Enhancement Processing Of Ovarian Ultrasound Images. - Saidin, Nafiza; Ngah, Umi Kalthum; Mashor, Mohd Yusoff (2003)

(untitled)
Image processing may be employed on ovarian ultrasound images to assist doctors in diagnostic analysis.